PUBLIC AND EDUCATIONAL ACTIVITY OF UKRAINIAN WRITERS IN VOLYN (20-30S OF THE XX CENTURY) - Pustovit, Hryhorii (Mountain School of Ukrainian Carpaty, 2020)
The article is devoted to the coverage of public and educational activities of Ukrainian writers in Volyn during the interwar period of the twentieth century. The literary process of the region, which was represented by such writers and publicists as O. Havryliuk, A. Zhyvotko, M. Levytskyi, O. Karpinskyi, O. Liatorynska, O. Stanchuk, H. Orlivna, K. Polishchuk, O. Levchanivska, A. Nyvynskyi, V. Ostrovskyi, P. Pevnyi, A. Richynskyi, I. Matviiuk, V. Myzynets, I. Stepaniuk, V. Kytaievskyi, M. Kalynchuk, H. Zhezhko, M. Cherkavskyi, I. Vlasovskyi, U. Samchuk and others, is characterized. The creative heritage and educational activities of individual writers who were teachers are analyzed. Their contribution to the promotion of Ukrainian culture, distribution of Ukrainian books, development of native language education and schooling is shown. It is concluded that the merit of Prosvita's activity in Volyn was the creation of Ukrainian-language secondary schools - Lutsk and Rivne Ukrainian private gymnasiums. Prosvita centers constantly took care of them: teachers-writers worked in these institutions; members of the society arranged special collections of monetary donations for the development of schools; Prosvita allocated part of the budget for their development, provided libraries with Ukrainian books, magazines, etc. Ukrainian writers and publicists (I. Vlasovskyi, A. Zhyvotko, M. Kalynchuk, O. Karpinskyi, O. Levchanivska, A. Nyvynskyi, V. Ostrovskyi, P. Pevnyi, A. Richynskyi, S. Semeniuk, etc.) patronized the national upbringing of children and youth by the means of native language. Through their efforts, separate departments for young readers were created in almost all libraries, including works by T. Shevchenko, Lesya Ukrainka, I. Franko, M. Gogol, P. Chaichenko, Marko Vovchok, P. Kulish, classics of foreign children's literature. “Traveling libraries” were arranged to popularize Ukrainian books and reading in general. These libraries, having from 10 to 50-60 books, traveled across the region and were addressed to the peasantry.